2022
DOI: 10.1093/bjs/znac039.232
|View full text |Cite
|
Sign up to set email alerts
|

348 The New Normal? – a Survey of Patients’ and Clinicians’ Satisfaction of Remote Consultations During the COVID-19 Pandemic

Abstract: Aim Remote consultations (RC) were implemented during the COVID-19 pandemic with the aim of preventing transmission of the virus. We conducted a survey to assess patients’ and clinicians’ satisfaction of RC. Method Two online surveys were created for patient and clinician feedback, and each recorded a cohorts' opinions on various aspects of RC. The surveys were distributed to Urology, General and Vascular surgery departments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Eleven studies were retrospective cohort studies12–19,21–23, and one was a case series 20 . Eleven studies were reported as a full text12,14–23 while one was an abstract from a poster presentation 13 . Of the 12 included studies, six studies reported data on patients with varying vascular conditions12–14,19,22,23, whereas the other six studies looked specifically at managing wounds including diabetic ulcers using telemedicine15–18,20,21.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eleven studies were retrospective cohort studies12–19,21–23, and one was a case series 20 . Eleven studies were reported as a full text12,14–23 while one was an abstract from a poster presentation 13 . Of the 12 included studies, six studies reported data on patients with varying vascular conditions12–14,19,22,23, whereas the other six studies looked specifically at managing wounds including diabetic ulcers using telemedicine15–18,20,21.…”
Section: Resultsmentioning
confidence: 99%
“…These studies took place in the United Kingdom 12 , 13 , Italy 16 , 18 , United States 21 , 23 and India 17 , 20 (two studies for each country). The other four studies were undertaken in Qatar, Australia, Colombia and China14,15,19,22.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations